Challenges and Approaches in the Development of Counseling Skills in University Students - Reza Pahlevi; Yusi Riksa (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: Counseling skills are essential for students in psychology, guidance counseling, and social work, as they are crucial for addressing psychological, emotional, and social issues effectively. Objective: This study aims to identify and analyze the factors influencing the development of counseling skills among university students, with particular emphasis on self-efficacy, cultural context, and the challenges encountered during training. Method: A systematic literature review was employed to gather, evaluate, and synthesize findings from empirical studies on counseling skills training for university students. This method enabled a structured and transparent collection of data from sources indexed in reputable academic databases. Results: The findings reveal that experiential learning methods, such as role-playing, internships, and case simulations, significantly improve students' empathy and interviewing skills. The use of technology, such as virtual reality (VR) simulations, also enhances non-verbal communication skills. Group supervision and feedback from peers and instructors accelerate the mastery of practical counseling skills. However, cultural differences and emotional stress during practice remain significant challenges. Conclusion: The study concludes that effective development of counseling skills requires a multimodal approach that integrates theory, practice, reflection, and feedback. It also emphasizes the need for adaptive curricula that take into account local and cultural contexts. Contribution: This research contributes to the design of more effective counseling training strategies, providing insights into how counseling programs can be adapted to meet the diverse needs of students from various cultural backgrounds.